Utilization of Digital Technology in Combating Stunting: Analysis of the Implementation of the Trengginas Application - Chusnul Zulaika; Ambar Dwi Erawati; Mona Tiorina Manurung (PT. Anagata Sembagi Education, 2024)
Malnutrition and stunting are significant public health issues that also impact the quality and capacity of human resources. Stunting, a chronic condition caused by prolonged inadequate nutritional intake, results in growth disorders, including shorter-than-average height and impaired brain development. These challenges can affect a child’s academic achievement, productivity, and creativity in later life. Addressing stunting requires comprehensive, collaborative strategies involving various stakeholders. This qualitative descriptive study examines the use of the Trengginas application as an innovative tool to detect and address stunting during the COVID-19 pandemic. Developed by the Semarang City Health Office, the Trengginas application allows stunting detection without requiring direct physical interaction with patients, aligning with pandemic restrictions. Data were collected through interviews with nutrition officers at the Mangkang Health Center, who are responsible for implementing the application. The study found that the Trengginas application requires minimal technical resources: a mobile phone, internet access, a WhatsApp account, and entry of the Population Identification Number and Family Card data. Nutrition officers play a central role in operating the application, which facilitates remote monitoring and intervention for stunting cases. This research highlights the potential of digital health innovations like the Trengginas application in addressing stunting challenges, especially during restrictive conditions such as a pandemic. By leveraging technology, the application supports efficient data collection and intervention delivery, making it a valuable tool in the effort to reduce stunting and improve child health outcomes in Semarang City